Intra-cervical foley’s catheter or PGE2 gel for induction of labour: which one is better: a prospective study - Kaur, Khushpreet; Kaur, Balwinder; Kaur, Navneet; Kaur, Gagandeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Labour is clinically defined as the initiation and perpetuation of uterine contraction with goal of producing progressive cervical effacement and dilatation. The Foley’s catheter is an effective alternative to prostaglandins for cervical ripening/labour induction. Study was done to compare the efficacy of intracervical Foley’s catheter and PGE2 gel as a cervical ripening agent and to study maternal and fetal outcome in terms of mode of delivery and Apgar score. Methods: This randomized controlled study was conducted in Obstetrics and Gynaecology department, Government Medical College, Patiala. 200 women with indication for induction of labour were enrolled in the study to investigate the efficacy and fetomaternal outcome of induction of labour with intracervical Foley’s catheter comparing with PGE2 gel. Results: The mean age in group A was 24.41±3.37 and in group B was 24.24±3.17 years. The 95% women were induced successfully in group A and 97% were successfully induced in group B. Preeclampsia and postdatism were the most common indications for induction in both groups. The mean induction delivery interval in group A was 15.20±4.53 hours and in group B was 15.86±4.79 hours. 4.21% cases required NICU admission in group A while in group B, it was 5.15% cases. Conclusions: Our study concludes that there is no difference in efficacy between intracervical Foley’s catheter and intracervical PGE2 gel for induction of labour and both methods are complementary to each other.